High SAA1 Expression Predicts Advanced Tumors in Renal Cancer - Li, Sen; Cheng, Yongbiao; Cheng, Gong; Xu, Tianbo; Ye, Yuzhong; Miu, Qi; Cao, Qi; Yang, Xiong; Ruan, Hailong; Zhang, Xiaoping (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) is the most frequent malignant tumor of the kidney. 30% of patients with RCC are diagnosed at an advanced stage. Clear cell renal cell carcinoma (ccRCC) is the most common pathological subtype of RCC. Currently, advanced ccRCC lacks reliable diagnostic and prognostic markers. We explored the potential of SAA1 as a diagnostic and prognostic marker for advanced ccRCC. In this study, we mined and analyzed the public cancer databases (TCGA, UALCAN and GEPIA) to conclude that SAA1 was up-regulated at mRNA and protein levels in advanced ccRCC. We further found that hypomethylation of SAA1 promoter region was responsible for its high expression in ccRCC. Receiver operating characteristic curve (ROC) indicated that high SAA1 levels could distinguish advanced ccRCC patients from normal subjects (p < 0.0001). Kaplan-Meier curve analysis showed that high SAA1 levels predicted poor overall survival time (p < 0.0001) and poor disease-free survival time (p = 0.0003). Finally, the functional roles of SAA1 were examined using a si-SAA1 knockdown method in RCC cell lines. Our results suggest that SAA1 may possess the potential to serve as a diagnostic and prognostic biomarker for advanced ccRCC patients. Moreover, targeting SAA1 may represent as a novel therapeutic target for advanced ccRCC patients.